1999
DOI: 10.1128/mcb.19.5.3727
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Mechanisms of Activation of Stat1 and Stat3 by Platelet-Derived Growth Factor Receptor in a Cell-Free System

Abstract: Ligand-dependent activation of the platelet-derived growth factor receptor (PDGFR) in fibroblasts in culture leads to the activation of the JAK family of protein-tyrosine kinases and of the transcription factors Stat1 and Stat3. To determine the biochemical mechanism of STAT activation by PDGFR, we devised a cell-free system composed of a membrane fraction from cells overexpressing PDGFR. When supplemented with crude cytosol, the membrane fraction supported PDGF-and ATP-dependent activation of both Stat1 and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
45
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 26 publications
2
45
0
Order By: Relevance
“…STAT1 activation seems to involve its direct interaction with the PDGF receptor, whereas STAT3 activation appears to require JAKs (51). Since multiple members of the JAK family can be activated by PDGF, it was suggested that each JAK is able to mediate STAT3 activation by PDGF independently (51). Our data are in agreement with the previous observation that JAK1 and JAK2 can be phosphorylated upon IGF-I stimulation (41).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…STAT1 activation seems to involve its direct interaction with the PDGF receptor, whereas STAT3 activation appears to require JAKs (51). Since multiple members of the JAK family can be activated by PDGF, it was suggested that each JAK is able to mediate STAT3 activation by PDGF independently (51). Our data are in agreement with the previous observation that JAK1 and JAK2 can be phosphorylated upon IGF-I stimulation (41).…”
Section: Discussionsupporting
confidence: 92%
“…This was shown by using the PDGF receptor mutant that was impaired in binding to Src. Furthermore, using cell-free system, it was demonstrated that the mechanisms of activation of STAT1 and STAT3 by PDGF are distinct (51). STAT1 activation seems to involve its direct interaction with the PDGF receptor, whereas STAT3 activation appears to require JAKs (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STAT3 is activated by tyrosine phosphorylation at a single site (Tyr-705) and by serine phosphorylation at 727 (Ser-727). Tyrosine phosphorylation of STAT3 in response to cytokine stimulation is mediated by a Janus kinase, and Src family members have been widely studied (17)(18)(19). Tyrosine phosphorylation is required for STAT3 dimerization, nuclear translocation, and DNA binding.…”
mentioning
confidence: 99%
“…The lack of dependency on ALK for STAT3 activation has been reported in many other human neoplasms that are ALKÀ, and multiple mechanisms of activating STAT3 also have been identified. 19,[36][37][38][39][40] More specifically, previous studies have shown that STAT3 activation may occur in a subset of ALKÀ ALCL 15,17 and in a subset of HL. 41,42 In addition to ALK and JAK3, several other oncogenic kinases, such as those encoded by the v-src, abl, v-fps, and v-sis genes, activate STAT3 in a direct and indirect manner.…”
Section: Discussionmentioning
confidence: 99%